The road to the economics of Brexit: a new direction in economic research - Mărginean, Silvia Cristina; Orăștean, Ramona; Sava, Raluca (Journal of Business Economics and Management, 2020)
Brexit became an important subject not only for academics but also for international institutions, research centers and consultancy companies, think tanks and independent experts. The aim of this article is to: (1) provide a general approach of the literature; (2) see how the effects of Brexit are explained in such short-term approach and how important are the economic issues in the debates; (3) identify directions for future research, arguing that a new field of study emerged. The estimation of economic impact of Brexit has generated a reach literature in a short period, which identifies the main issues, rather than providing strong results and conclusions. In order to fill this gap, our paper provide a systematic review of the most important contributions and group them in four research directions: overall economic implications of Brexit; Brexit and trade; migration and labour market; financial issues and Brexit.